2018
DOI: 10.5430/jnep.v8n12p105
|View full text |Cite
|
Sign up to set email alerts
|

A study of school bag weight and back pain among intermediate female students in Dammam City, Kingdom of Saudi Arabia

Abstract: Background: The most common cause of low back pain in children is muscle sprain and strain which can occur from carrying a heavy backpack or from activities. This study aimed to assess the relationship between school bag weight and back pain among female students in Dammam city.Methods: A total of 300 female students were included in this study both from east and west sectors of Dammam city, Saudi Arabia. Tools: Data were collected using (1) A structured questionnaire sheet including, socio-demographic data of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
1
8
1
1
Order By: Relevance
“…The results of the present study revealed that school students were mostly used to carrying schoolbags on one side (60.2%). However, this finding is not in agreement with the results of other studies [1,6,26,27], which reported that most students carried their schoolbags over two shoulders.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of the present study revealed that school students were mostly used to carrying schoolbags on one side (60.2%). However, this finding is not in agreement with the results of other studies [1,6,26,27], which reported that most students carried their schoolbags over two shoulders.…”
Section: Discussioncontrasting
confidence: 99%
“…Among the 10 studies which were not included in the meta‐analyses, only one suggested that LBP was more prevalent among the children who carried schoolbags representing a higher percentage of their bodyweight, especially among boys (vs. girls), with the percentage of the bodyweight associated with a higher risk for LBP being smaller when the children were younger (Grimmer & Williams, ). None of the other nine studies which were not included in the meta‐analysis, found such an association (Alghamdi et al, ; Chiang et al, ; Johnson et al, ; Korovessis et al, ; Mwaka et al, ; Noormohammadpour et al, ; Oka et al, ; Watson et al, ; Young et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Sample size of the studies ranged between 55 and 4,813. Three studies included only children (Angarita‐Fonseca et al, ; de Oliveira et al, ; Vidal et al, ), and three studies included only teenagers (Akbar et al, ; Alghamdi et al, ; Noormohammadpour et al, ), while all the others included both children and teenagers. Two studies included only girls (Alghamdi et al, ; Noormohammadpour et al, ) while all the others included both boys and girls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations